Case Method Learning Model in Increasing Student Participation in Early Childhood Laboratory Management Course - Pangaribuan, Tumewa; Amanada, Rizky Surya; Yusra, Affan (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to see the influence of the case method learning model to increase student participation in ECCE laboratory management courses. This research uses the type of Classroom Action Research (PTK). The research subjects were 29 semester 5 students. The research was carried out in two cycles, namely cycle 1 and cycle 2. The data collection technique used is an observation technique. The analytical techniques used in this study use quantitative descriptive data analysis techniques with descriptive statistics. The results showed that the case method learning model can increase student participation in learning.